The CARBA-MAP study: national mapping of carbapenemases in Spain (2014–2018) - Gracia-Ahufinger, Irene; López-González, Laura; Vasallo, Francisco José; Galar, Alicia; Siller, María; Pitart, Cristina; Bloise, Iván; Torrecillas, Miriam; Gijón-Cordero, Desirée; Viñado, Belén; Castillo-García, Javier; Campo, Rainer; et al. (Frontiers in Microbiology, 2023)
Infections caused by carbapenem-resistant Enterobacterales (CRE) and carbapenemresistant Pseudomonas aeruginosa, including isolates producing acquired carbapenemases, constitute a prevalent health problem worldwide. The primary objective of this study was to determine the distribution of the different carbapenemases among carbapenemase-producing Enterobacterales (CPE, specifically Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae complex and Klebsiella aerogenes) and carbapenemase-producing P. aeruginosa (CPPA) in Spain from January 2014 to December 2018. A national, retrospective, cross-sectional multicenter study was performed. The study included the first isolate per patient and year obtained from clinical samples and obtained for diagnosis of infection in hospitalized patients. A structured questionnaireThis study was sponsored and funded by MSD Spain was completed by the participating centers using the REDCap platform, and results were analyzed using IBM SPSS Statistics 29.0.0. A total of 2704 carbapenemase-producing microorganisms were included, for which the type of carbapenemase was determined in 2692 cases: 2280 CPE (84.7%) and 412 CPPA (15.3%), most often using molecular methods and immunochromatographic assays. Globally, the most frequent types of carbapenemase in Enterobacterales and P. aeruginosa were OXA-48-like, alone or in combination with other enzymes (1523 cases, 66.8%) and VIM (365 cases, 88.6%), respectively. Among Enterobacterales, carbapenemase-producing K. pneumoniae was reported in 1821 cases (79.9%), followed by E. cloacae complex in 334 cases (14.6%). In Enterobacterales, KPC is mainly present in the South and South-East regions of Spain and OXA-48-like in the rest of the country. Regarding P. aeruginosa, VIM is widely distributed all over the country.